ANALISIS KATA PINJAMAN BAHASA INGGRIS DALAM ISTILAH BIOLOGI BAHASA INDONESIA - PONTOH, CHINDY CRISTY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ  Â  Â  Â  Â  Â  Â  Â  Â Â This research entitled â€œAnalisis Kata Pinjaman Bahasa Inggris dalam Istilah Biologi Bahasa Indonesiaâ€.The objectives of research are to find out the kinds and the changes of the meanings of English loanwords in Indonesian language. In analysing the data, the writer uses Haugenâ€™s theory to find out the types and Baughâ€™s theory to get the changes of the meanings. To support the analysis, the writer uses Oxford Dictionary and Kamus Besar Bahasa Indonesia.The result of this research show that based on the theory of Haugen there are three kinds of loanword. Those are loanword without phonemic substitution, loanword with partial phonemic substitution, loanword with complete phonemic substitution and there are two kinds of the changes of meaning such as extension, narrowing, regeneration, and degeneration.Â Keywords: Loanwords, Changes of meaning, Biological terminology,Sociolinguistics